ENOQUE: UM LIVRO PROFÉTICO PARA O CRISTO - Guimarães, Filipe de Oliveira (2015)
Until the fourth century AD, was common among Christians, to read the book of I Enoch. The embryo of rejection began in the second century, with Julius Africanus, and reached its peak in the fourth century with Augustine of Hippo. However, the official position, in Western Christianity, which rejected the writing of I Enoch as a useful literature to faith, happened at the Council of Laodicea (century IV) who said that the only names of angels authorized by the Scriptures would be the Miguel, Gabriel and Raphael. this position deleted the book of Enoch (book that makes reference to several names of angels) from the books useful for theological research, until recent times in the West. The great character of Christianity was a man recognized in Palestinian as Rabbi. This title presupposes knowledge of the main literature enjoyed by the Jews. The consensus among most of the Second Temple scholars, is that the writing of I Enoch occupied a distinct place in the literary scene of that time. This thesis was born from a plausible suspicion, which is embedded within the cultural context of the I century AD, that Jesus knew the Book of I Enoch. But not only that, distrust develops in the possibility that he has studied the writing and he built teachings based on that text. The research had as general objective: Find the relationship between Jesus of Nazareth and the Written I Enoch. With regard to its technical procedures, research is bibliographic, exploratory and documentary. For this research to gain form, we used the historiographical proposal of the Historical Jesus, and have developed a methodology called Analysis of the Sayings of Jesus (ASJ), for use in the investigation of sayings attributed to Jesus contained in the Gospels. The first chapter, besides being a book review of I Enoch addressing the book on various perspectives, was built aiming to bring the Brazilian Academy the latest information on research related to I Enoch, in dialogue with the principal investigators of this literature. The second chapter was developed in order to examine by historiography, the potential of some words recorded in the Gospels in being originates from the person of Jesus. The third and last chapter presents an approach among words that were examined and the Book of I Enoch. The end result indicates that the literature of Enoch may have occupied a prominent place among the estimated written by Jesus Christ.